Inheritance of primary and secondary oat grain weight - Cabral, Cândida Braga; Milach, Sandra Cristina Kothe; Crancio, Leonardo Araripe; Pacheco, Marcelo Teixeira (Pesquisa Agropecuaria Brasileira, 2002)
The development of varieties with high grain physical quality, yield and adaptation is one of the main objectives of the oat breeding programs in the South of Brazil. Grain weight is one of the criteria used to determine oat quality and, in order to define the best strategies for the improvement of this trait, it is important to study its genetic basis. Until now, studies of this nature have not been conducted with the Brazilian oat genotypes. This work was carried out with the objective of studying the inheritance of primary and secondary oat grain weight. Samples of 20 primary and secondary grains of a variable number of plants from the generations P1, P2, F1, F2 and F3 from five crosses were weighted. From these data, frequency distributions, variances and the predominant gene effects were obtained and heritability values were estimated in the broad sense and using the parent-offspring regression. The results showed that there is variability in early generations for the weight of primary and secondary grains and that additive and dominance are the main acting gene effects. The presence of major genes was not detected in the expression of these traits. Continuous variation in the F2 generation and low to moderate heritabilities indicate that low selection pressures are recommended in early generations.